Clinical evaluation of the efficacy of Khadiradi yoga avachoornana in Kachchu with special reference to genitoinguinal intertrigo - Mamatha, K. V. (Medknow Publications Pvt Ltd, 2010)
Kachchu is a simple localized dermatological infection of the genitoinguinal region, which occurs because of unhygienic observance, and manifests in the form of inflammation followed by secondary bacterial or fungal infections that can be best correlated to genitoinguinal intertrigo. Even though it rarely causes systemic manifestations, its mere presence itself is disturbing because of intractable itching and pain. It may delay the proper healing of the episiotomy wound and may cause difficulty in walking because of severe pain. Candida powder is the highest selling medicine for the intertrigo, as the incidence of intertrigo is as high as 40% in some particular seasons. In the Ayurveda fraternity, there is no established preparation that can be preserved safely in all the epochs of life in females and which is easy to apply. After understanding the disease in the perspective of the ayurvedic and modern medicinal systems, Khadiradi yoga choorna — a new ayurvedic formulation — was prepared on the basis of stringent ayurvedic principles. Hence, an attempt has been made to study the efficacy of the khadiradi yoga avachurnana(1) in Kachchu, with special reference to genitoinguinal intertrigo in females.